Percentage of Pancasila student profile dimensions in the Merdeka curriculum and the implications for high school guidance and counseling programs - Fausta, Thadeus Ega; Muslihati, Muslihati; Indreswari, Henny (Univeritas Papua, 2024)
The Merdeka curriculum is an improvement on the previous curriculum, namely the 2013 curriculum, whose implementation was based on the implementation of the Pancasila student profile. The aim of this research is to compare the six dimensions of the Pancasila student profile in order to assist counselors in developing guidance and counseling service programs. This research uses a survey method. The research subjects were 90 students in class X at a private Catholic high school in Malang. The results of data analysis in this study found that the percentage of the dimensions of faith, devotion to God Almighty, and having noble morals was 80.56%, the global diversity dimension was 72.83%, the mutual cooperation dimension was 81.61%, the independent dimension was 83.78%, the critical reasoning was obtained at 81.50%, and the creative dimension was obtained at 77.67%. The findings of this study can be utilized as a point of reference for counselors to design guidance and counseling programs in schools to enhance or maintain values that strengthen dimensions within the Pancasila student profile. This includes collaborating with subject teachers, conducting group guidance, using traditional games, art therapy, and various counseling techniques.